1994
DOI: 10.1159/000276617
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Method to Record Changes in Nasal Reactivity during Treatment of Non-Allergic Nasal Hyperreactivity

Abstract: Non-allergic nasal hyperreactivity is a common problem and many patients suffer from daily symptoms demanding medication. Hitherto there exists no objective method to study congestional changes in clinical practice, to evaluate the efficacy of different therapies. This study is an attempt to develop a method for this purpose. Eleven patients with non-allergic nasal hyperreactivity entered the trial. A histamine challenge model with three different histamine concentrations was used. Recordings of the reactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Therefore, there is a need for an objective method of measuring changes in mucosal swelling in patients with nasal hypereactivitiy. This finding is in line with the results reported by others who argue that symptom scores alone are not sufficient for studying changes in the degree of hyperreactivity [21].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, there is a need for an objective method of measuring changes in mucosal swelling in patients with nasal hypereactivitiy. This finding is in line with the results reported by others who argue that symptom scores alone are not sufficient for studying changes in the degree of hyperreactivity [21].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with rhinitis medicamentosa are clinically identical with patients having vasomotor rhinitis with nasal blockage as their main symptom. We have previously reported that 14 days of treatment with budesonide nasal spray significantly reduced the histamine sensitivity in patients with vasomotor rhinitis [14].…”
Section: Discussionmentioning
confidence: 88%
“…This is probably because oedema was still present after treatment. In two other studies it has also been suggested that the rebound congestion in rhinitis medicamentosa results from interstitial oedema, because of incomplete decongestion after the application of an ·-agonist [1,14]. Patients with rhinitis medicamentosa are clinically identical with patients having vasomotor rhinitis with nasal blockage as their main symptom.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients with vasomotor rhinitis have an increased sensitivity to histamine compared with healthy subjects, 22 and 14 days' treatment with topical nasal corticosteroids reduces nasal reactivity and symptoms. 23 Likewise, Stjärne and coworkers 24 treated therapy-resistant patients with vasomotor rhinitis with capsaicin, a substance known to activate unmyelinated C fibers, with a depletion of vasoactive substances. These patients reported a positive effect on nasal symptoms for up to 6 months before nasal symptoms recurred.…”
Section: Commentmentioning
confidence: 99%